Towards an understanding of the release behavior of temperature-sensitive liposomes: a possible explanation of the "pseudoequilibrium" release behavior at the phase transition temperature. (19th March 2013) - Zhang, Xin; Luckham, Paul F.; Hughes, Alun D.; Thom, Simon; Xu, Xiao Yun
Abstract: It is generally believed that thermal sensitive liposomes (i.e. vesicles) that contain 1, 2-dihexadecanoyl-sn-glycero-3-phosphocholine (DPPC) and 1, 2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethyleneglycol)-2000 (DSPE.2000) maintain a constant permeability to ionic molecules when they are heated to the phase transition temperature of the membrane ( T m ). However, DPPC:DSPE.2000 liposome systems have been reported to release encapsulated agent in a "pseudoequilibrium" pattern upon temperature rise, whereby there is a rapid release of encapsulated material followed by no further release. Little effort has been made to determine the mechanism of such release behavior. We aim to explore the potential cause of "pseudoequilibrium" release of DPPC:DSPE.2000 liposome systems in response to temperature rise. Using calcein as a hydrophilic marker, the release pattern of DPPC:DSPE.2000 liposome system at T m has been carefully determined. The potential mechanism of its release behavior has been further explored using two novel assays (i.e. heating–cooling–reheating assay and incubation assay). Our results show that there is a dramatic enhancement of the permeability of DPPC:DSPE.2000 vesicles to ionized molecules (i.e. calcein) during the initial period of heating to 42 °C. This is believed to result from the opening of the hydrophilic pores at the liquid/solid interface. However, after less than 2 min of incubation at this temperature, no further release of calcein is observed, suggesting that the sizes of pores are reduced, restricting any further movement of calcein molecules. On cooling and reheating the DPPC:DSPE.2000 liposomes to 42 °C, no further release of calcein is observed. The incorporation of MSPC (1-stearoyl-2-hydroxy-sn-glycero-3-phosphocholine) extends the release period of calcein from the DPPC:MSPC:DSPE.2000 vesicles to more than 30 min, suggesting that the lysolipid stabilizes the pores in the lipid membrane.